2022
DOI: 10.12968/bjhc.2021.0074
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition for medical documentation: an analysis of time, cost efficiency and acceptance in a clinical setting

Abstract: Background/Aims Medical documentation is an important and unavoidable part of a health professional's working day. However, the time required for medical documentation is often viewed negatively, particularly by clinicians with heavy workloads. Digital speech recognition has become more prevalent and is being used to optimise working time. This study evaluated the time and cost savings associated with speech recognition technology, and its potential for improving healthcare processes. Methods Clinicians were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although, conversational agents are seen as useful (Bibault et al, 2019; Inkster et al, 2018) and easy to use (Cameron et al, 2019). Zuchowski and Göller (2022) reported that health care professionals preferred to type medical notes, rather than dictate using speech recognition software. Speech recognition software reduces the amount of time to complete medical documentation.…”
Section: Ai‐based Qas In Health Carementioning
confidence: 99%
“…Although, conversational agents are seen as useful (Bibault et al, 2019; Inkster et al, 2018) and easy to use (Cameron et al, 2019). Zuchowski and Göller (2022) reported that health care professionals preferred to type medical notes, rather than dictate using speech recognition software. Speech recognition software reduces the amount of time to complete medical documentation.…”
Section: Ai‐based Qas In Health Carementioning
confidence: 99%
“…A randomized study from 2015 showed an increase in productivity by physicians using this technology ( 64 ). In the meantime, speech recognition software has been shown to be faster and more accurate than typing, but the acceptance by clinicians still leaves a lot to be desired ( 65 ).…”
Section: The Perspective Of Human Languagementioning
confidence: 99%
“…Once pressed, recording will commence immediately and will not stop until the system recognizes that the user has spoken something and then stopped speaking. This is the main input modality for telling the system to take in user input, and the only way for the system to initiate recognition and subsequently synthesize a response as propsed in [28]- [32]. Finally, the show/hide output button can be pressed to show or hide the area below the button which automatically records the conversation being had as visual text data.…”
Section: Proposed Mechanism Of Speech Recognitionmentioning
confidence: 99%